Approximate Behaviors as Cues for Addressing Learning Needs - Ocampo, Jr., Jose M; Ocampo, Laura V (Universitas Pendidikan Indonesia, 2018)
ABSTRACT: The behavior of learners can serve as cue, so that teachers would make the necessary adjustments in handling the class. However, when this behavior becomes intolerable, some people call it misbehavior. In this light, behavior which is usually recognized as distressing can be viewed with optimism. Too much hand and body movement of children inside or outside classroom can be viewed as indicating a favorable need for action, a call for alternative process to achieve learning. This study attempted to present an alternative view of first grade learnersâ€™ behavior during reading sessions in class. For gathering of data, a checklist was used to observe one participant-learner every scheduled reading class. The first grade learnersâ€™ reading difficulties can be manifested through various behaviors. These behaviors are grouped and can be observed on four areas, such as head, arm-hand, shoulder-waist, and waist-foot. The approximate behaviors as cues for addressing learning needs have similar postures found in brain gym movements. It is recommended that other areas of learning difficulty among school learners be explored. Further, identify the learning difficulties in reading and the behaviors of school learners using the checklist constructed by the researchers.KEY WORD: Behavior; Cues for Learning Needs; Learning Difficulty; Brain Gym Movements.Â ABSTRAKSI: â€œPerkiraan Perilaku sebagai Isyarat untuk Mengatasi Kebutuhan Belajarâ€. Perilaku peserta didik dapat dijadikan isyarat, sehingga guru dapat melakukan penyesuaian yang diperlukan dalam penanganan kelas. Namun, bila perilaku ini menjadi tidak tertahankan, beberapa orang menyebutnya perilaku salah. Dalam hal ini, perilaku yang biasanya dikenali sebagai hal yang menyedihkan dapat dilihat dengan optimisme. Terlalu banyak gerakan tangan dan tubuh anak-anak di dalam atau di luar kelas dapat dipandang sebagai indikasi kebutuhan tindakan yang baik, sebuah panggilan dalam proses alternatif untuk mencapai pembelajaran. Penelitian ini mencoba menyajikan pandangan alternatif tentang perilaku peserta didik di kelas satu selama sesi membaca di kelas. Untuk pengumpulan data, daftar isian ceklis digunakan dalam mengamati satu peserta didik di setiap kelas pembacaan yang dijadwalkan. Kesulitan membaca peserta didik kelas satu dapat diwujudkan melalui berbagai perilaku. Perilaku ini dikelompokkan dan dapat diamati pada empat bidang, seperti kepala, lengan-tangan, bahu-pinggang, dan pinggang-kaki. Perkiraan perilaku sebagai isyarat untuk mengatasi kebutuhan belajar memiliki postur tubuh serupa yang ditemukan pada gerakan asah otak. Disarankan agar daerah lain yang mengalami kesulitan belajar di antara siswa sekolah dapat dieksplorasi. Selanjutnya, identifikasi kesulitan belajar membaca dan perilaku pelajar sekolah menggunakan daftar isian ceklis yang disusun oleh para peneliti.KATA KUNCI: Perilaku; Isyarat untuk Kebutuhan Belajar; Kesulitan Belajar; Gerakan Asah Otak. Â Â About the Authors: Jose M. Ocampo, Jr., Ph.D. is a Full Professor at the Faculty of Education Sciences PNU (Philippine Normal University) in Manila, Philippines. Laura V. Ocampo, M.A. is a Science Grade School Teacher at the Claret School of Quezon City, Philippines. For academic interests, the authors are able to be contacted via e-mails at: juno_6970@yahoo.com and hope4619@gmail.comSuggested Citation: Ocampo, Jr., Jose M. Laura V. Ocampo. (2018). â€œApproximate Behaviors as Cues for Addressing Learning Needsâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 3(1), March, pp.1-10. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Article Timeline: Accepted (February 8, 2018); Revised (March 11, 2018); and Published (March 30, 2018).